Idiopathic Interstitial Pneumonia in the ICU: An Observational Cohort Study. Issue 6 (November 2015) - Martinez, F. E.; Panwar, R.; Kelty, E.; Smalley, N.; Williams, C.
In the absence of a clearly identifiable cause, the prognosis of patients with interstitial lung disease is grim. This study describes our institutional experience in management of patients who are admitted to an ICU with respiratory insufficiency secondary to idiopathic interstitial pneumonia (IIP). This study was performed to obtain Australian data on patients admitted to an ICU with respiratory insufficiency secondary to IIP. This is a retrospective cohort study of patients with IIP who were admitted to the ICU between December 2007 and December 2013 at one of two university-affiliated academic hospitals in Newcastle, New South Wales. Thirty-six patients (69% male) were admitted to the ICU in respiratory insufficiency from IIP. The median age of the cohort was 71 (66 to 77) years. The median APACHE III score was 68 (56 to 97). Sixty-nine percent (25/36) of patients died in hospital. The median ICU and hospital lengths of stay were 6 (2 to 13.5) and 12 (4.8 to 18.3) days respectively. No significant difference was observed between admission characteristics and mortality. Patients admitted to ICU with respiratory failure secondary to IIP are aggressively investigated and treated, but still have a high mortality rate. Accurate predictors of mortality would be useful in offering aggressive treatment to patients who would benefit from it.